Biodiversité des gastropodes terrestres de la willaya Souk Ahrass et évaluation de la sensibilité de (Cemulla virgata) aux Herbicides (Topik 80). - HADDAD Hayet; HADJAJ Maroua (My University, 2020)
Our research aims to carry out the space-time inventory (autumn, winter, spring and summer) of teressite gasterropods in several wilaya resorts Souk ahras in eastern Algiria (Souk ahras, Sedrata, M'daourouche and Ain soltane).And to assess and examine herbicide toxicity (Topik 80) on Cernulla Virgata (good pollution bioindicator) during exposure. The samples were conducted from October 2019 to Jalliet 2020, the inventory was completed by a biometric and morphological study and then to present the defefers species of terrestress gasterropods or the biodiversity of terrestrial gasterropods refocused in the sites of studies of wilaya Souk ahras.The reglued species are: 10 species of Earth Gasteropods divided as follows: the Limacidae family with the slug species Milax nigricans (Phillipi, 1836) and the Milacidae family with the slug Milax gagates (Draparnaud, 1801); the Hygromiidae family with Cernuella virgata (Da Costa, 1778); the Helicidae family with Helix aperta (Born, 1778), Helix sprinkled (Muller, 1774), Helix constantinae (Forbes, 1838) and Hilix milanostoma), Otala lactea (Muller, 1774); the Subulinidae family with Rumina decollata (Linnaeus, 1758); and the Cochlicellidae family with cochlicella acuta (Draparnaud, 1801). The different ecological indicators of the stand were calculated for each site (abundance, total wealth, average wealth, frequency of occurrence, relative frequency, diversity and equitability). The most abundant species are: cernulla virgata and H. aperta. -------------------------------------------------------------------------------- اعتمدنا في بحثنا على عملية الجرد المكاني والزماني( الخريف-الشتاء-الربيع-الصيف) للرخويات البرية في بعض مناطق ولاية سوق اهراس في الشرق الجزائري (سوق اهراس-سدراتة-عين سلطان-مداوروش) وبالاضافةالى تقييم سمية مبيد الاعشاب (توبيك 80 )علىدليل جيد للتلوث البيئي(Cernuella virgata)عملية الجرد تمت من شهراكتوبر(2019) الى شهر جويلية (2020).انتهت عملية الجرد بالحصول على دراسة بيومترية ومورفولوجية وايضا عرض مختلف الرخويات البرية او التنوع البيولوجيي للرخويات المتحصل عليها في مختلف الدراسة لولاية سوق اهراس.الانواع المتحصل عايها هي(10) انواع من الرخويات موزعة كما يلي.عائلةLimacidae مع l'espèce de limace Milaxnigricans (Phillipi, 1836) وعائلة Milacidae مع limace Milaxgagates (Draparnaud, 1801); عائلة Hygromiidae معCernuellavirgata (Da Costa, 1778); عائلةHelicidaeمعHelixaperta (Born, 1778), Helixaspersa (Müller, 1774), Helix constantinae (Forbes, 1838) وHilixmilanostoma), Otala lactea (Muller, 1774) ; عائلةSubulinidaeمعRumina decollata (Linnaeus, 1758) ;وعائلةCochlicellidae معCochlicellaacuta(Draparnaud, 1801) كما تم حساب مؤشرات بيئية لكل موقع. وفرة الثروة الاجمالية. متوسط الثروة. تواتر حدوث. التكرار النسبي و التوزيع المتساوي.الانواع الاكثر وفرة هي HelixapertaوCernuella virgata ---------------------------------------------------------------------------- Notre recherche menée aréaliser l’inventaire et l’étude de la distribution spatio-temporel (automne, hiver, printemps et été) des gastéropodes terrestres dans plusieurs stations de wilaya Souk ahras en est d’Algérie (Souk ahras, Sedrata, M’daourouche et Ain soltane)., mais la deuxième contribuassions articule sur l’évaluation de la toxicité aigue d’un herbicides (Topik 80) au espèce non cible comme « Cernulla virgata » (bon bioindicateur de pollution) durant l’exposition.Les échantillonnages ont été menées d’Octobre 2019 à Juillet 2020de réaliser unelistes des différentes espèces des gastéropodes terrestres ou bien la biodiversité de la Malacofaune terrestres récentes dans4 sites d’études de wilaya Souk ahras.Les espèces récoltés sont: 10 espèces de Gastéropodes Terrestres se répartissant comme suit: la famille des Limacidae avec l'espèce de limace Milax nigricans (Phillipi, 1836) et la famille des Milacidae avec la limace Milax gagates (Draparnaud, 1801); la famille des Hygromiidae avec Cernuella virgata (Da Costa, 1778); la famille Helicidae avec Helix aperta (Born, 1778), Helix aspersa (Müller, 1774), Helix constantinae (Forbes, 1838) et Hilix milanostoma), Otala lactea (Muller, 1774) ; la famille des Subulinidae avec Rumina decollata (Linnaeus, 1758) ;et la famille des Cochlicellidae avec Cochlicella acuta(Draparnaud, 1801). Les différents indices écologiques du peuplement ont été calculés pour chaque site (abondance, richesse totale, richesse moyenne, fréquence d’occurrence, fréquence relative, diversité et équitabilité). Les espèces les plus abondantes sont: Cernulla virgata et H. aperta.